1H-NMR study of the lambda operator site OL1: assignment of the imino and adenine H2 resonances. - Weiss, M A (1984)
One- and two-dimensional proton NMR methods are being used to study the synthetic lambda operator site O-L1, a 17 base-pair DNA duplex recognized by lambda repressor and Cro protein. The complete assignment of the 17 imino protons, which participate in Watson-Crick hydrogen bonding, and of the eight adenine H2 protons, which lie in the minor groove of the double helix, is presented.